The Scope of Education Management and Alignment with Advances in Digital Technology - Puji Ambarwati; Anis Zohriah (Studia Manageria, 2024)
The government of Indonesia encourages the maximum use of information and computer technology in education in order to achieve a more effective and efficient performance framework. This is also to achieve a better quality of education.. The purpose of this research is to describe how the scope of education management aligns with the current advances in digital technology in several educational institutions in Indonesia. This research is a qualitative research with literature method. The literature method is carried out by analyzing data derived from several reading sources such as books, journals and relevant previous research results. The results of this research show that the implementation of aspects within the scope of education management in several educational institutions in Indonesia can be aligned with the development and utilization of digital technology at this time. The right alignment between education management and the advancement of digital technology that has been widely used in educational institutions in Indonesia ranging from PAUD levels to secondary schools and universities is expected to improve the quality of education in Indonesia.